Influence of the Glass Transition on Rotational Dynamics of Dyes in Thin Polymer Films. Single Molecule and Ensemble Experiments - Araoz, Beatriz (2014)
We performed polarized fluorescence emission studies of Nile Red (NR) in poly(methyl methacrylate) (PMMA), poly(ethyl methacrylate) (PEMA), and poly(butyl methacrylate) (PBMA) at the single molecule (SM) and at the ensemble level to study the in cage movements of the ground-state molecule in polymer films of nanometric thickness at room temperature. Experiments were performed with wide field irradiation. At the ensemble level, the linearly polarized irradiation was used to induce a photoselection by bleaching, which is compensated by rotational diffusion. Both results show an appreciable difference in mobility of NR in the films that is correlated with the different glass-transition temperatures of the films, particularly in PEMA, which displays a clearly distinct behavior between the 200 nm films, representing a rigid environment, and the 25 nm ones, showing much higher mobility. We developed a model of broad application for polarized photobleaching that allows obtaining rotational diffusion coefficients and photobleaching quantum yields in an easy way from ensemble experiments. The parameters obtained from ensemble measurements correlate well with the results from SM experiments.